RESEARCH KNOWLEDGE, ATTITUDES AND RELATED FACTORS ON SAFE SEX OF STUDENTS AT MY XUYEN HIGH SCHOOL, CAN THO CITY (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the proportion of students with correct knowledge and good attitudes on safe sex and to identify several related factors of students at My Xuyen High School, Can Tho city.Subjects and methods: A cross-sectional descriptive study was conducted on 403 students at My Xuyen High School from September to December 2024. A structured questionnaire was used to assess students knowledge and attitudes on safe sex.Results: The proportion of students with correct knowledge on safe sex was 66.5%, among them, knowledge on sexually transmitted infections, particularly HIV/AIDS, was the highest at 99.3%, while only 16.5% students recognized hepatitis B as an sexually transmitted infections. The proportion of students with good attitudes on safe sex was relatively low, accounting for 21.3%. The statement “using contraceptive methods indicates safe sexual practices” received the highest level of agreement (67.7%). However, 45.6% students still felt embarrassed when buying or asking about condoms. Knowledge level was associated with academic performance, and attitudes on safe sex were influenced by gender.Conclusions: The percentage of students with correct knowledge and good attitudes on safe sex is not high. It is necessary to enhance sexual safety education for high school students, particularly those with lower academic performancea nd male students as a key target group to improve knowledge and adjust attitudes toward sexual safety.
Keywords: Safe sex, knowledge, attitudes, high school students.